2014
DOI: 10.1371/journal.pntd.0003145
|View full text |Cite
|
Sign up to set email alerts
|

A Target Repurposing Approach Identifies N-myristoyltransferase as a New Candidate Drug Target in Filarial Nematodes

Abstract: Myristoylation is a lipid modification involving the addition of a 14-carbon unsaturated fatty acid, myristic acid, to the N-terminal glycine of a subset of proteins, a modification that promotes their binding to cell membranes for varied biological functions. The process is catalyzed by myristoyl-CoA:protein N-myristoyltransferase (NMT), an enzyme which has been validated as a drug target in human cancers, and for infectious diseases caused by fungi, viruses and protozoan parasites. We purified Caenorhabditis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Further studies will be necessary to follow up on these findings and titrate minimal effective concentrations of drug with activity against adult filarial worms. Interestingly, inhibition of filarial NMT proved to be very effective in our screen, confirming previous data of Galvin et al [ 27 ]. In that study, NMT was shown to be essential for viability in both B .…”
Section: Discussionsupporting
confidence: 92%
“…Further studies will be necessary to follow up on these findings and titrate minimal effective concentrations of drug with activity against adult filarial worms. Interestingly, inhibition of filarial NMT proved to be very effective in our screen, confirming previous data of Galvin et al [ 27 ]. In that study, NMT was shown to be essential for viability in both B .…”
Section: Discussionsupporting
confidence: 92%
“…The enzyme myristoyl-CoA:protein N -myristoyltransferase (NMT) has recently been validated as a promising drug target in trypanosomiasis ( Frearson et al., 2010 ) and malaria ( Wright et al., 2014 ), diseases caused by the protozoan parasites Trypanosoma brucei and species of Plasmodium , respectively. NMT has also been proposed as a potential drug target for infections caused by parasitic nematodes ( Galvin et al., 2014 ) and for the leishmaniases ( Price et al., 2003 ). NMT catalyzes a protein modification, the attachment of the C14:0 lipid myristate (Myr, tetradecanoic acid, Figure 1 A) to the N-terminal glycine residue of specific target proteins in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…N-myristoyltransferase (NMT), an enzyme which has been validated as a drug target in human cancers, and for infectious diseases caused by fungi, viruses, and protozoan parasites. Galvin et al 83 purified C. elegans and B. malayi NMTs as active recombinant proteins and carried out kinetic analyses with their essential fatty acid donor, myristoyl-CoA, and peptide substrates. The genetic and chemical studies performed in the study highlighted the importance of myristoylation in the synthesis of functional proteins in nematodes and have shown, for the first time, that NMT is required for viability in parasitic nematodes.…”
Section: Article In Pressmentioning
confidence: 99%